ANALISIS STRUKTUR MODAL SERTA PENGARUHNYA TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA TAHUN 2007-2010 - Aswin Kurniawan (Jurnal Riset Bisnis Indonesia, 2013)
This research aims to examine asset growth, return on asset, current ratio, sales growth, andcompany benchmark on capital structure, as well as their impact on company value. The sampleof this research is 79 companies with characteristic: (1) manufacture companies which are listed inIndonesia Stock Exchange in the period of 2007-2010; (2) companies that publish financial statementfor four consecutive years in the period of 2007-2010; (3) companies which do not experience lossin the period of 2007-2010. The analysis technique of this research uses multiple linear regressionanalysis. The results show that the factors of asset growth, sales growth, and company benchmarksignificantly bring positive impact on capital structure. Then, current ratio and sales growth significantlybring negative impact on capital structure. However, capital structure brings no impact on companyvalue.Keywords: Asset Growth, Return on Asset, Current Ratio, Sales Growth, company benchmark,capital structure, company value.